Power supply optimization method based on multivariate load peak-valley complementary characteristics. Issue 1 (1st March 2023) - Yue, Guo; Yudi, Ding; Yunfei, Wang; Huan, Yan; Xiaoxiao, Geng
Abstract: The power grid load shows a trend of diversified development. With the continuous increase of the power grid construction scale, it is very important to optimize the power supply of the distribution network and improve the utilization of assets and equipment by using the peak valley complementary characteristics of multiple loads. In this paper, the peak-valley fluctuation characteristics of load are classified and analyzed. Cluster analysis is used to study the load classification with stable peak-valley characteristics in the complex load composition. Based on the peak-peak superposition and peak-valley complementary characteristics of the classified load, and considering the load space dimension, the multi-load optimization combination method for the whole period and time segment is proposed, and verified by simulation.